Smart cleaning cotton fabrics cross-linked with thermo-responsive and flexible poly(2-(2-methoxyethoxy)ethoxyethyl methacrylate-co-ethylene glycol methacrylate). Issue 48 (28th May 2015) - Zhong, Q.; Chen, Y. Y.; Guan, S. L.; Fang, Q. S.; Chen, T.; Müller-Buschbaum, P.; Wang, J. P.
<x xml:space="preserve">Abstract</x> The smart cleaning ability of cotton fabrics is realized by cross-linking thermo-responsive random copolymer to the cotton.